2004
DOI: 10.1111/j.1743-6109.2004.04025.x
|View full text |Cite
|
Sign up to set email alerts
|

Earliest Time to Onset of Action Leading to Successful Intercourse with Vardenafil Determined in an At-Home Setting: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Introduction Vardenafil, a potent and selective oral PDE5 inhibitor, is efficacious and generally well-tolerated in men with erectile dysfunction (ED). Of considerable interest to patients and physicians is an understanding of the time required after dosing to attain penile erection sufficient for successful sexual intercourse. Aim To determine the earliest time to onset of action of vardenafil 10 and 20 mg leading to success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 16 publications
1
20
0
2
Order By: Relevance
“…The present study showed that vardenafil effectively improves EF compared with placebo, consistent with the findings of other clinical studies with vardenafil [11][12][13][14][15][16][17][18][19]. For the primary efficacy variable (change in IIEF-EF domain score at week 12), the analysis showed a highly statistically significant difference in favor of vardenafil (P < 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that vardenafil effectively improves EF compared with placebo, consistent with the findings of other clinical studies with vardenafil [11][12][13][14][15][16][17][18][19]. For the primary efficacy variable (change in IIEF-EF domain score at week 12), the analysis showed a highly statistically significant difference in favor of vardenafil (P < 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…The onset of action of PDE5i has been defined in clinical trials and all 3 drugs may offer good response in some patients in about 15min; sildenafil may be successful in 35% of men after 14 min, tadalafil in 32% after 16 min, while vardenafil in 23% after 11min [63][64][65]. In the everyday clinical practice however, such data may lead to misuse of the drugs and an increased number of non-responders.…”
Section: Pde5i: Unanswered Questionsmentioning
confidence: 96%
“…Such success rates are important for patient confidence and compliance with treatment, 23 and 19 whereas in the ReliabilityVardenafil for Erectile Dysfunction I (RELY-I) study, first-dose penetration success rates ranged from 75 to 84% for patients with diabetes, dyslipidemia and hypertension. 23 Further placebo-controlled studies have shown the rapid onset of action of vardenafil, with more than 50% of participants achieving erections within 25 min, 24 and as rapidly as 15 min. 25 The incidence of AEs in this study was low and comparable with previous studies.…”
Section: Discussionmentioning
confidence: 99%